Analysis of Chromate Transporters in Bacterial Species for Cr(VI) Reduction Isolated from Tannery Effluent Contaminated Site of Dindigul District, Tamil Nadu, India. Issue 7 (1st July 2021) - Selvakumar, Princy; Subramanian, Devika; Natarajan, Jeyakumar; Solai Ramatchandirane, Prabagaran
Abstract: Leather industries are well-known causative for hexavalent chromium [Cr(VI)] pollution in the environment. This possess a greater risk to human survival and disruption of ecological balance. Conventional methods to manage chromium through physical and chemical processes are mostly expensive and generate subsequent solid wastes which are cumbersome to treat. Hence, biological treatment is often regarded as the alternative method employing microorganisms for detoxification of Cr(VI). In this investigation, almost 32 bacterial strains were isolated from Dindigul district of Tamil Nadu, India. Among them, five isolates showed exceptional Cr(VI) reduction within 48 h upon aerobic cultivation. Bacteria confers chromium resistance through Chr transporters which involve metabolic reduction of toxic Cr(VI) to nontoxic Cr(III) through reductase enzyme. Activity by this enzyme are often associated with soluble proteins located in cytosol of the cell. Existence of chromate ( Chr ) transporters in identified isolates were confirmed in their genome through bioinformatics tools, where their structures were predicted based on Protter, a web-based tool. Conclusively, bacterial strains that could evolve as potential ones to reduce toxic Cr(VI) to its nontoxic Cr(III) form in chromium contaminated sites.